A review of the gekkonid genus Calodactylodes (Reptilia: Squamata) from India and Sri Lanka - Bauer, Aaron M.; Das, I. (Wildlife Heritage Trust of Sri Lanka, 2000)
Gekkonid lizards of the genus Calodactylodes are endemic to peninsular India and Sri Lanka. The genus consists of two species, C. aureus and C. illingworthorum (formerly C. illingworthi) and is diagnosable on the basis of derived digital structure, the presence of paraphalanges, bright yellow gular patch (at least in adult males), and distinctive vocalisation. The skeletal, hemipenial, and external morphology of both species is described. Field observations of C. aureus at Vellore, Tamil Nadu, indicate that males are highly vocal and that communal egg-laying occurs. Calodactylodes aureus appears to be common in appropriate habitats and is probably more widely distributed than previously believed. Relationships of Calodactylodes to other gekkonids remain obscure but may reflect Gondwanan origins.